Pola peresepan antibiotik pada pasien infeksi saluran kemih di instalasi rawat jalan RSUD Provinsi NTB tahun 2017 - Dwi Herlina; Raisya Hasina; Ni Made Amelia Ratnata Dewi (Sasambo Journal of Pharmacy, 2021)
Urinary tract infection (UTI) is an infection due to the proliferation of microorganisms in the urinary tract. UTI is usually occur in the community at various ages. In 2014, Indonesian Ministry of Health showed that the number of people with UTIs reached 90-100 cases per 100,000 population per year. Antibiotics are the main therapy used in treating urinary tract infections. The purpose of this study was to determine the pattern of antibiotic prescribing in UTI patients and determine the suitability of therapy with guidelines for UTI at the Installation of NTB Provincial Hospital in 2017. The design of this study was descriptive by collecting data retrospectively. The study was conducted on 105 UTI patients at the Installation Hospital of NTB Province in 2017, then the data obtained from the medical record and prescription sections were processed using Microsoft Excel software. The results showed that therapy for UTI patients was antibiotics with the most use of ciprofloxacin (45.71%), then cefixime (40%), urinter (pipemidic acid) (11.43%), levofloxacin (1.90%), cefadroxil (0.95 %). Based on these results, the suitability of prescription was seen from the type of drug and the dosage in the main therapy (antibiotics) was 100% according to the treatment guidelines, but the frequency and duration of administration only reached 99.05% and 88.6%.